Artificial intelligence in science and society: The vision of USERN - Dorigo, Tommaso; Brown, Gary D.; Casonato, Carlo; Cerdà, Artemi; Ciarrochi, Joseph; da Lio, Mauro; D’Souza, Nicole; Gauger, Nicolas R.; Hayes, Steven C.; Hofmann, Stefan G.; Johansson, Robert; Liwicki, Marcus; et al. (Institute of Electrical and Electronics Engineers, 2025)
The recent rise in relevance and diffusion of Artificial Intelligence (AI)-based systems and the increasing number and power of applications of AI methods invites a profound reflection on the impact. The Universal Scientific Education and Research Network (USERN), an organization that promotes initiatives to support interdisciplinary science and education across borders and actively works to improve science policy, collects here the vision of its Advisory Board members, together with a selection of AI experts, to summarize how we see developments in this exciting technology impacting science and society in the foreseeable future. In this review, we first attempt to establish clear definitions of intelligence and consciousness, then provide an overview of AI’s state of the art and its applications. A discussion of the implications, opportunities, and liabilities of the diffusion of AI for research in a few representative fields of science follows this. Finally, we address the potential risks of AI to modern society, suggest strategies for mitigating those risks, and present our conclusions and recommendations